A new genus and species of the tribe Oemini (Coleoptera, Cerambycidae, Cerambycinae) from the Sundaic region, Southeastern Asia - Niisato, Tatsuya; Vives, Eduard; Heffern, Daniel (Zootaxa, 2020)
A new genus and species of the subtribe Oemina of the tribe Oemini (Cerambycidae: Cerambycinae) is described from the Sundaic region, Southeastern Asia. Relationships with other oemine genera are discussed.